Straw Returning Methods Affects Macro-Aggregate Content and Organic Matter Content in Black Soils: Meta-Analysis and Comprehensive Validation - Kangmeng Liu; Yu Hu; Yumei Li; Lei Wang; Liang Jin; Lianfeng Cai; Xiaoxiao Wu; Zhenguo Yang; Yan Li; Dan Wei (Plants)
Straw returning into the soil is a crucial method for boosting soil carbon levels. To research the influence of straw return practices on soil aggregates and organic matter content within the farmlands of the Northeast Black Soil Region, the objective was to clarify the varying impacts of these practices on soil carbon enhancement. In this study, 89 pertinent papers were acquired through a rigorous literature compilation. Meta-analysis and the linear regression method were employed to analyze the influence of field return methods, their duration on soil water-stable aggregates, and their organic matter content. Furthermore, the study delved into the trends in the variation of aggregates and organic matter in relation to mean annual temperature and precipitation. Our results showed that the straw-returning method has been discovered to predominantly bolster soil organic matter by altering the proportions of macro-aggregate content. Specifically, straw incorporation has led to a notable enhancement in the content of macro-aggregates (57.14%) and micro-aggregates (20.29%), in addition to augmenting the content of macro-, small, and micro-aggregate organic matter by 13.22%, 16.43%, and 15.08%, respectively. The most significant increase in large agglomerates was witnessed in straw return over a period of more than 5 years (115.17%), as well as shallow mixing return (87.32%). Meanwhile, the highest increase in the organic matter content of large agglomerates was recorded in straw return over 5 years (12.60%) and deep mixing return (8.72%). In the field validation experiment, a period of seven years of straw return significantly boosted the macro-aggregate content across various soil layers, ranging from 11.78% to 116.21%. Furthermore, among the various climatic factors, the primary determinants of disparities in study outcomes were the average annual temperature and average annual precipitation. Specifically, lower precipitation and higher temperatures were conducive to the enhancement of macro-aggregate formation and organic matter content.